Localized wrinkling of metal films on elastic and liquid substrates - Yi Sun; Liping Yan; Benyong Chen; Wei Song; Filippo Berto (Fracture and Structural Integrity)
Global and localized wrinkling phenomena in films/substrates have been widely studied by means of experiment and theoretical analyses in the past two decades. They have shown broad application prospect in microstructure manufacture. The global wrinkling patterns with well-defined wavelengths can be readily fabricated in the polymer films, the metal films and the surface of modified elastic substrates by O2 plasma or UVO, and they have attracted much attention. For the localized wrinkling patterns, however, most previous studies were limited to polymer films, which while metal films were not properly considered. Recent studies have shown that wrinkles can be localized by constrained edges and cracks in metal films deposited on the elastic and liquid substrates. In this review, we focus on the formation and evolution mechanisms of these localized wrinkle patterns, and we aim to provide some useful guidance for future studies on designing the localized wrinkling patterns with real-time controllable dimension, orientation and morphology in the films/substrates.